The BrainHealth Databank: a systems approach to data-driven mental health care and research - Santisteban, Jose Arturo; Rotenberg, David; Kloiber, Stefan; Maslej, Marta M.; Ansari, Adeel; Amani, Bahar; Courtney, Darren; Farrokhi, Farhat; Freeman, Natalie; Hassan, Masooma; Kwan, Lucia; Mozuraitis, Mindaugas; et al. (Frontiers in Neuroinformatics, 2025)
IntroductionMental health care is undermined by fragmented data collection, as incomplete datasets can compromise treatment efficacy and research. The BrainHealth Databank (BHDB) at the Centre for Addiction and Mental Health (CAMH) establishes the governance and infrastructure for a Learning Mental Health System that integrates digital tools, measurement-based care, artificial intelligence (AI), and open science to deliver personalized, data-driven care.MethodsCentral to the BHDB’s approach is its comprehensive governance framework, which actively engages clinicians, researchers, data scientists, privacy and ethics experts, and patient and family partners. This codesigned approach ensures that digital health technologies are deployed ethically, securely, and effectively within clinical settings.ResultsBy aligning data collection with clinical and research goals and harmonizing over 12 million data points from 33,000 patient trajectories, the BHDB enhances data quality, enables real-time decision support, and fosters continuous improvement.DiscussionThe BHDB provides a model for integrating AI and digital tools into mental health care, as well as research data collection, analyses, storage, and sharing through the BHDB Portal (https://bhdb.camh.ca).